2007
DOI: 10.1007/s00213-006-0671-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of morphine and cocaine in M1 muscarinic acetylcholine receptor-deficient mice

Abstract: These results suggest a modulatory role of the M1 muscarinic receptor in opioid antinociception and conditioned drug reward, and demonstrate the utility of M1 receptor knockout models for the determination of the role of the M1 subtype in the behavioral effects of morphine and cocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007). Lack of galanin may therefore increase availability of ACh, thus increasing the sensitivity of GKO mice to opiates.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007). Lack of galanin may therefore increase availability of ACh, thus increasing the sensitivity of GKO mice to opiates.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine- and cocaine- induced conditioned-place preference are attenuated by either genetic disruption of the M 1 muscarinic receptor or combining drug treatments with an antagonist for the M 1 receptor [144]. In these studies, knock-out or antagonist treated animals correspond to State A in Figure 1, with wild-type and vehicle treated animals corresponding to State B in which activation of the M 1 receptor allows ACh to facilitate food- or drug- reinforced behaviors.…”
Section: A Threshold Model For Cholinergic Effects On Reinforced Behamentioning
confidence: 99%
“…These neuropharmacological properties have been associated with its weak stimulant effects in tests of locomotor activity and place preference (Li et al 2005). The antimuscarinic actions of AHN-1055 might be important, as muscarinic receptor stimulation is needed, at least in part, to generate drug-induced reward and reinforcement (Carrigan and Dykstra 2007;Crespo et al 2006). While neurochemical and behavioral evidence would support the potential use of this analog as a candidate treatment in cocaine addiction, neither its reinforcing nor its motivational properties, as measured in cost-benefit and relapse assays, have been previously investigated.…”
mentioning
confidence: 99%